2010
DOI: 10.1111/j.1439-0531.2009.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐Associated Glycoprotein and Progesterone Concentrations during Pregnancy Failure in Bedouin Goat from the Southwest of Algeria

Abstract: Thirteen female Bedouin goats living in arid land of Algeria Sahara desert were used in this study. These goats were pregnant but they sustained an abortion because of unidentified causes. None of the goats showed any signs of general disease. Plasma concentrations of caprine pregnancy-associated glycoproteins (cPAGs) and progesterone (P4) were determined during pregnancy using radioimmunoassay. The cPAGs concentration was undetectable (<0.8 ng/ml) throughout the first 2 weeks of gestation. From week 3 after m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…This breed acquires its importance from its perfect adaptation to the harsh environmental conditions of its biotope [1] . This has been confirmed by various ecophysiological and metabolic studies [2][3][4] . Considering the paramount importance for this community, goat's production level must be maintained properly by increasing fertility and conception rate [5] .…”
Section: Introductionsupporting
confidence: 65%
“…This breed acquires its importance from its perfect adaptation to the harsh environmental conditions of its biotope [1] . This has been confirmed by various ecophysiological and metabolic studies [2][3][4] . Considering the paramount importance for this community, goat's production level must be maintained properly by increasing fertility and conception rate [5] .…”
Section: Introductionsupporting
confidence: 65%
“…Several ecophysiological and metabolic studies have demonstrated their adaptive physiological characteristics to arid areas. Indeed, in these animals, the reduction of water turnover and glomerular filtration rates is observed [1], and high levels of placental pregnancy-associated glycoproteins are produced, which maintain gestation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has conducted several studies on this local breed, focusing on its reproductive endocrine ecophysiology and pathophysiology [2][3][4][5][6] and endocrine and metabolic response in the Saharan environment [7,8]. Recently, the performance of lactating goats based on relationships between milk yield and udder morphological traits was investigated [9].…”
Section: Introductionmentioning
confidence: 99%
“…Bedouin goat has also low metabolic requirements and can reduce its energetic metabolism and digest low quality diet during food restriction periods (Silanikove, Tagari, & Shkolnik, 1993). Furthermore, Bedouin goat has higher concentration of caprine Pregnancy-Associated Glycoproteins, reflecting a strategy of adaptation for maintaining a pregnancy under arid conditions (Charallah, Amirat, Sulon, Khammar, & Beckers, 2009), and after kidding, it ensures the survival of its offspring by maintaining its milk production in such environment. In fact, Bedouin goat living in Negev desert and Eastern Sinai showed a high daily milk yield and was able to maintain its milk production unchanged after 2 days of dehydration Shkolnik, Maltz, & Gordin, 1980).…”
Section: Introductionmentioning
confidence: 99%